1989
DOI: 10.1530/jrf.0.0870001
|View full text |Cite
|
Sign up to set email alerts
|

Development of the seminiferous tubules after neonatal hemicastration in the boar

Abstract: Summary. Development of the prepubertal seminiferous tubules of the right testis was characterized morphometrically every 14 days from 10 to 122 days of age in intact boars (I)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Whilst total Sertoli cell numbers at 25 dpp are the reciprocal of mature Sertoli cell numbers, early termination of mitosis in MS boars would result in a smaller adult Sertoli cell population and smaller testes compared with WC boars. These observations are consistent with the appearance of lumina by 28 dpp and early onset of spermatogenesis (56 dpp) in MS boars (Lunstra et al 1997), contrasting initiation of lumen formation by 94 dpp (Kosco et al 1989), and completion by 120 dpp (Tran et al 1981) in WC boars. These observations further illustrate the considerable breed differences in timing of Sertoli cell maturation and blood-testis barrier formation, and thus duration of the Sertoli cell proliferation period.…”
Section: Discussionsupporting
confidence: 76%
“…Whilst total Sertoli cell numbers at 25 dpp are the reciprocal of mature Sertoli cell numbers, early termination of mitosis in MS boars would result in a smaller adult Sertoli cell population and smaller testes compared with WC boars. These observations are consistent with the appearance of lumina by 28 dpp and early onset of spermatogenesis (56 dpp) in MS boars (Lunstra et al 1997), contrasting initiation of lumen formation by 94 dpp (Kosco et al 1989), and completion by 120 dpp (Tran et al 1981) in WC boars. These observations further illustrate the considerable breed differences in timing of Sertoli cell maturation and blood-testis barrier formation, and thus duration of the Sertoli cell proliferation period.…”
Section: Discussionsupporting
confidence: 76%
“…The porcine spermatogenesis during the postnatal development is not well understood because of the limited number of studies (Kosco et al 1989, Franca et al 2000, Goddard et al 2001. c-kit is known to be a protooncogene encoding a tryrosine kinase receptor in the PDGF/CSF-1 receptor family (Yarden et al 1987, Qiu et al 1988.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the signal of porcine c-kit mRNA was utilized as a control in the present study, and was observed in the testes at all stages from day 13 to adult stage. Porcine male germ cells have been reported to proliferate continuously in seminiferous tubules during postnatal stages (Kosco et al 1989, Franca et al 2000. The diameter of seminiferous tubules and number of spermatogenic cells have been shown to increase gradually from day 94 to 122, and the onset of spermiogenesis has been observed at day 94 (Kosco et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of these steps to FSH has also been shown in mature rats treated with a GnRH antagonist [37] or immunized against GnRH [28] as well as in juvenile and adult monkeys [5,27,41] and hpg mice [36]. Finally, hemicastration of boars at a young age has also been shown to increase Sertoli cell numbers in the remaining testis [26,33] accompanied by a transient increase in blood FSH levels [25].…”
mentioning
confidence: 99%